2009
DOI: 10.1097/prs.0b013e31819346b5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Computed Tomographic Imaging Measurements with Clinical Findings in Children with Unilateral Lambdoid Synostosis

Abstract: Mastoid bossing, skull base cant, and inferior ear deviation ipsilateral to the fused sutures were clinical findings that were consistent with computed tomographic measurements in these patients. Trapezoid head shape and posterior ear deviation were not. Radiographic suture fusion was observed in all cases; however, the extent of fusion did not correlate with the degree of deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…Other diagnostic criteria (clinical and radiologic), however, can be used to secure the diagnosis. 2,3 Clinically, the most consistent feature of isolated unilateral lambdoid craniosynostosis seems to be the ipsilateral occipitomastoid bossing. Other methods, such as using the overall skull shape as a diagnostic tool, can be tricky, because Lossee et al showed that lambdoid synostosis takes on a trapezoid shape in a vertex view and a parallelogram shape from a posterior view.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other diagnostic criteria (clinical and radiologic), however, can be used to secure the diagnosis. 2,3 Clinically, the most consistent feature of isolated unilateral lambdoid craniosynostosis seems to be the ipsilateral occipitomastoid bossing. Other methods, such as using the overall skull shape as a diagnostic tool, can be tricky, because Lossee et al showed that lambdoid synostosis takes on a trapezoid shape in a vertex view and a parallelogram shape from a posterior view.…”
Section: Discussionmentioning
confidence: 98%
“…Their distinction has historically been unclear, because similar clinical characteristics cause a true dilemma to arise. [1][2] Historically, Muakkassa et al described lambdoid craniosynostosis with the ear displaced anteroinferiorly. Muakkassa et al 7 published data on 64 cases of unilateral lambdoid synostosis and commented on the ear position (anterior in all cases); however, as Mulliken et al 8 points out, Muakkassa most likely over-reported cases of true lambdoid synostosis by including cases of posterior positional plagiocephaly in his cohort, and for that reason, his description of 64 cases of unilateral lambdoid synostosis has been excluded from this literature review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several distinguishing features have been previously presented. [1][2][3] According to these, a true ULC can be distinguished from PPP by the posterior bossing in the mastoid area in the synostotic side to the flat part of the lambdoid head. However, PPP is also noted to sometimes cause frontal bossing ipsilateral to the flat part of the head.…”
mentioning
confidence: 98%
“…This condition is frequently confused with posterior positional plagiocephaly (PPP), which is a common craniofacial deformity caused by external forces on the skull during periods of craniofacial growth and maturation. [1][2][3][4] The clinical diagnostic features of ULC and PPP have considerable overlapping. Both skull types have calvarial deformities such as flattening of the occipital region.…”
mentioning
confidence: 99%